Natural fiber staining and reinforcement with PLA from pineapple stubble as potential textile - Jirón, Eddy (2022)
For this paper, natural fibers obtained from pineapple stubble were stained using red, olive green, black and orange synthetic anilines to later make textiles reinforced with a polylactic acid biopolymer (PLA). The fibers were obtained from the stubble by decorticating the leaves and then applying three different treatments: sodium hydroxide (5 %), sodium dodecyl sulfate (8.6 mmol/L), and ethanol (70 %). Later, they were compacted by adding PLA, pressure and temperature to form the textile in order to add strength and record its color change. The color difference in the fibers was measured before and after applying heat into the textile by means of the CIELAB system. At the end of the process, it was determined that the greatest change registered after the thermal unification during the experimentation was that of the orange aniline treated with ethanol, which had a magnitude ∆E* = 331,41.